Frailty and sarcopenia among Turkish people aged 40 and above living with HIV. Issue 10 (19th April 2022) - Houssein, Mehdi; Inkaya, Ahmet Çagkan; Balci, Cafer; Esme, Mert; Sönmezer, Meliha Çağla; Unal, Serhat; Halil, Meltem Gülhan
Abstract: Background: People living with HIV face a variety of challenges, including accelerated ageing and geriatric syndromes. In this study, we aimed to examine the prevalence of frailty and sarcopenia among Turkish people living with HIV. Methods: In total, 100 people living with HIV were recruited in this study. Frailty was determined using Fried's frailty phenotype, and we calculated the Charlson Comorbidity Index, Veterans Aging Cohort Study (VACS) index, fracture risk assessment tool scores, and Mini‐Mental State Exam scores. We determined muscle mass using bioelectric impedance analysis, gastrocnemius muscle thickness using ultrasonography, and muscle strength using handgrip strength. Results: The mean ± standard deviation age was 50.0 ± 8.3 years. In total, 11% of the patients were frail. The risk of comorbidity and mortality, VACS index, and 5‐year mortality risk was significantly higher in the frail group, as was sarcopenia. Fat‐free muscle mass and handgrip strength were correlated with gastrocnemius muscle thickness. Gastrocnemius muscle thickness suggestive of sarcopenia was defined as 13.05 mm. The cognitive impairment rate was 5% and was associated with physical frailty. Conclusion: Frailty is common and associated with higher morbidity and mortality rates among Turkish people living with HIV.